Evaluation of Effectiveness of Umbilical Cord Cryoextract in Aesthetic Medicine (in Vitro Study) - Shevchenko , Nadiia; Terekhova, Olena; Kaverinska, Anna; Prokopiuk , Olga; Lazurenko , Viktoriya; Prokopіuk , Volodymyr (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(2):133-138